Activation of constitutive androstane receptor (CAR) in primary human hepatocytes - Maclennan, Richard Alexander (2016)
Human populations are at risk of exposure to constitutive androstane receptor (CAR) activators present in a range of substances, including pharmaceuticals, plasticizers and crop protection agents. What exposure to CAR activators means for human health is uncertain. Activation of CAR in rodents is associated with liver hyperplasia, increased proliferation and eventual hepatocarcinoma; however the effect in human hepatic cells is unclear. There are two methods by which a compound can achieve activation of CAR; directly or indirectly via cellular signalling pathways. Phenobarbital is a prototypical activator of CAR and does so in an indirect manner via suppression of epidermal growth factor receptor (EGFR) signalling. Direct activation of CAR in rodents also causes hepatocellular carcinoma but the human outcome is less clear. We have carried out microarray and miRNA analysis of CITCO (a potent and selective hCAR ligand) treated primary human hepatocytes. To mitigate the well documented effect of primary hepatocyte dedifferentiation primary hepatocytes were cultured in dynamic three dimensional culture in vitro. Gene expression changes indicate that direct activation of hCAR causes the promotion of a pro-proliferative and anti-apoptotic phenotype. The miRNA expression profile is crucially different to rodent data that is currently published. Despite the pro-proliferative phenotype shown there is no evidence that primary human hepatocytes proliferate in response to direct activation of CAR by CITCO. This leaves the possibility that a proliferative response may be observed in vivo or that the changes in gene expression are solely a human physiological adaptation to direct hCAR activation by CITCO and no proliferation would occur. The effect on human health and liver toxicity is unclear but this body of work has provided data that may be used to further understand the mechanistic effects of direct hCAR activation in human hepatocytes. A more complete understanding of this will help to inform the toxic potential of direct hCAR activation in vivo.